Age-Related Variations in Intestinal Microflora of Free-Range and Caged Hens - Cui, Yizhe; Wang, Qiuju; Liu, Shengjun; Sun, Rui; Zhou, Yaqiang; Li, Yue (Frontiers in Microbiology, 2017)
Free range feeding pattern puts the chicken in a mixture of growth materials and enteric bacteria excreted by nature, while it is typically unique condition materials and enteric bacteria in commercial caged hens production. Thus, the gastrointestinal microflora in two feeding patterns could be various. However, it remains poorly understood how feeding patterns affect development and composition of layer hens’ intestinal microflora. In this study, the effect of feeding patterns on the bacteria community in layer hens’ gut was investigated using free range and caged feeding form. Samples of whole small intestines and cecal digesta were collected from young hens (8-weeks) and mature laying hens (30-weeks). Based on analysis using polymerase chain reaction denaturing gradient gel electrophoresis (PCR-DGGE) and sequencing of bacterial 16S rDNA gene amplicons, the microflora of all intestinal contents were affected by both feeding patterns and age of hens. Firmicutes, Bacteroidetes, Actinobacteria, Proteobacteria and Fusobacteria were the main components. Additionally, uncultured environmental samples were found too. There were large differences between young hens and adult laying hens, the latter had more Firmicutes and Bacteroidetes, and bacterial community is more abundant in 30-weeks laying hens of all 6 phyla than 8-weeks young hens of only 2 phyla. In addition, the differences were also observed between free range and caged hens. Free range hens had richer Actinobacteria, Bacteriodetes and Proteobacteria. Most of strains found were detected more abundant in small intestines than in cecum. Also the selected Lactic acid bacteria from hens gut were applied in feed and they had benefitial effects on growth performance and jejunal villus growth of young broilers. This study suggested that feeding patterns have an importance effect on the microflora composition of hens, which may impact the host nutritional status and intestinal health.